1984
DOI: 10.1002/1097-0142(19841015)54:8<1645::aid-cncr2820540828>3.0.co;2-q
|View full text |Cite
|
Sign up to set email alerts
|

Extrapulmonary oat cell carcinoma

Abstract: Primary extrapulmonary tumors with histologic features indistinguishable from bronchogenic oat cell carcinoma are appearing with increasing frequency in the literature. These tumors have been described in the esophagus, stomach, pancreas, larynx, hypopharynx, salivary glands, nasal cavity and paranasal sinuses, thymus, small and large bowel, uterine cervix, endometrium, breast, prostate, urinary bladder, and skin. It is now widely believed that oat cell carcinoma is a poorly differentiated counterpart of carci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
87
0
11

Year Published

1988
1988
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 284 publications
(101 citation statements)
references
References 115 publications
3
87
0
11
Order By: Relevance
“…These include its rarity (Remick et al, 1987;Acea Nebril et al, 1996), the predominance of older patients (Medgyesy et al, 2000;Maitra et al, 2001), the characteristic presentation (Wick et al, 1987;Hoff and Pazdur, 1999), including occasional symptoms that are secondary to hormone production (Taniguchi et al, 1973;Chejfec and Gould, 1977;Doherty et al, 1984) and the typical advanced stage at diagnosis (Matsui et al, 1991;Bennouna et al, 2000). The high proportion of oesophageal tumours is also in agreement with previous reports (Ibrahim et al, 1984;Remick et al, 1987); 30% of our patients and half of the cases reported in the literature had oesophageal tumours. In concordance with the literature, the colon and rectum was the leading location in our study, involved in 39% of the patients (Hoff and Pazdur, 1999).…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…These include its rarity (Remick et al, 1987;Acea Nebril et al, 1996), the predominance of older patients (Medgyesy et al, 2000;Maitra et al, 2001), the characteristic presentation (Wick et al, 1987;Hoff and Pazdur, 1999), including occasional symptoms that are secondary to hormone production (Taniguchi et al, 1973;Chejfec and Gould, 1977;Doherty et al, 1984) and the typical advanced stage at diagnosis (Matsui et al, 1991;Bennouna et al, 2000). The high proportion of oesophageal tumours is also in agreement with previous reports (Ibrahim et al, 1984;Remick et al, 1987); 30% of our patients and half of the cases reported in the literature had oesophageal tumours. In concordance with the literature, the colon and rectum was the leading location in our study, involved in 39% of the patients (Hoff and Pazdur, 1999).…”
Section: Discussionsupporting
confidence: 94%
“…In light of its rarity, and the fact that it was so far studied from an organ-centred perspective, data with regard to this entity is extremely limited. Owing to the paucity of information and its resemblance to the well-recognised primary SmCC of the lung (Kelsen et al, 1980;Fer et al, 1981;Ibrahim et al, 1984), the disease is usually managed as the latter (Nichols and Kelsen, 1989;Huncharek and Muscat, 1995). However, the extent of the similarity between the two entities has been recently questioned; data from a literature review that we have performed (Brenner et al, 2004), as well as from other reports, suggest some differences between the two (Nishimaki et al, 1997;Arai and Matsuda, 1998;Takubo et al, 1999;Maitra et al, 2001).…”
mentioning
confidence: 99%
“…Small cell carcinoma can also arise in the bladder, uterine cervix, esophagus, large intestine, ovary, pancreas, prostate, stomach and thymus. The morphological features as well as clinical aggressiveness are quite similar to those of SCLC (Galanis et al, 1997;Ibrahim et al, 1984;Murren et al, 2001), but ordinary carcinoma, such as squamous cell carcinoma and adenocarcinoma, presents together with small cell carcinoma rather often.…”
Section: Introductionmentioning
confidence: 87%
“…Extrapulmonary SNEC represents 4 percent of all SNECs [1]. Less than 270 cases of head and neck SNEC have been published till March, 2006 including 69 cases of SNEC in nasal and paranasal sinuses in world literature [3].…”
Section: Discussionmentioning
confidence: 99%
“…Small cell neuroendocrine carcinoma (SNEC) of head and neck is very rare and has been reported only since 1965 [1,2]. Due to its rarity the understanding of pathology of the disease and planning for ideal treatment have been diffi cult.…”
Section: Introductionmentioning
confidence: 99%